Perkembangan Ilmu Komunikasi Islam - Hefni, Harjani (Jurnal Komunikasi Islam, 2014)
Conducting research towards a knowledge will strengthen the status and the object of scientific study. Cla–rity object of study will make the assessment becomes more focused, while the validity of the source will make the science becomes solid. While the existence of the college will make the science of growing. This article discusses the communication perkembangan Islam, both scientifically and institutionally. The author argues that the building of com–munication science Islam began to develop in the 20th cen–tury. The development is influenced by the development of science communication, especially when the technologies of communication and communication media is growing ra–pidly in line with the needs of human nature as social human.Keywords: Communication sciences of Islam, the development, the object of study, the validity of the source----------------------------------------------------------------------Melakukan Penelitian yang terus menerus terhadap sebuah ilmu pengetahuan akan memperkuat status dan objek kajian ilmu pengetahuan tersebut. Kejelasan objek kajian akan membuat kajian menjadi semakin fokus, sedangkan validitas sumber akan membuat ilmu menjadi kokoh. Sedangkan keberadaan perguruan tinggi akan membuat ilmu semakin berkembang. Artikel ini membahas perkembanagan komunikasi Islam, baik secara keilmuan maupun institusional. Penulis berpendapat bahwa bangunan ilmu komunikasi Islam mulai berkembang di abad ke-20. Perkembangan tersebut dipengaruhi oleh perkembangan il–mu komunikasi, terutama ketika tehnologi komunikasi dan media komunikasi berkembang pesat seiring dengan kebu–tuhan fitrah manusia sebagai makhuk sosial.Kata Kunci: Ilmu komunikasi Islam, perkembangan, obyek kajian, validitas sumber